Pendampingan Program Kartu Prakerja Agar Ramah untuk Difabel Dalam Perspektif Difusi Inovasi: Pendampingan Program Kartu Prakerja Agar Ramah untuk Difabel Dalam Perspektif Difusi Inovasi - Dini Hidayanti Herpamudji (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2022)
Unemployment in Indonesia is an increasingly complicated problem. The pre-employment card program with an online training system is here to be one solution. However, only 3 percent of the participants were disabled. This shows that there are problems in the adoption of innovations in this online and digital program. The study was conducted in Prov. Central Java is the area with the third-highest percentage of disabled people (12.61%) in Indonesia based on Sakernas in 2020. The method used is library research. Followed by an in-depth interview with 4 selected informants. It aims to review the government's efforts to assist the Pre-employment Card program for people with disabilities. With results include: (a) The Adoption Decision Process by The Disabled varies both in the stages of Knowledge, Persuasion, Decision, Implementation, and confirmation. (b) The role of opinion leaders and innovators is important in the communication channels assisting pre-employment card programs. (c) Reinvention occurs when this program is considered difficult to understand by people with disabilities, especially the visually impaired to utilize other applications to support participating in the program. So it can be shown that until now the implementation of the program: (1) Not yet friendly for people with disabilities because there are no special tools that can help that are integrated into the program. (2) Assistance of persons with disabilities for pre-employment card programs still needs to be done.